Save, Even If It’s a Penny”: Transnational Financial Socialization of Black Immigrant Women - Bertranna A. Muruthi; Kimberly Watkins; Megan A McCoy; Kenneth J White; Amanda Stafford McRell; Michael Thomas; Abiola Taiwo (Journal of Financial Therapy, 2020)
The purpose of this study is to investigate Black-Caribbean and African women’s transnational financial socialization. Analysis of the data show 1) financial socialization in the country of origin: (a) parents stressed the importance of saving, (b) learned about money management explicitly, (c) learned about money management through observation, (d) learned by observing parent’s struggle; and 2) the impact to women’s financial navigation in the U.S.: (a) not receiving financial education, (b) unexpected financial stressors in the U.S., (c) difficulty saving, (d) the need for more financial education. Implications for mental health and financial practitioners and researchers are provided.
Keywords: financial socialization; immigrants; black immigrants; transnational; financial management